The Role of Glu/Gly/Zif-8 Edible Film in Improving the Superior Rheological and Water Vapor Barrier Properties and Antibacterial Activity for Active Food Packaging - Djenar, Nancy Siti; Rinaldi, Kardian; Rahma, Dina Nur; Kustiana, Dina (Departemen Kimia, 2026)
The low barrier to water vapor and gas is a critical limitation of glycerol-plasticized gluten-based edible films (GBEF) for food packaging applications. In this study, gluten (Glu) and glycerol (Gly) were cross-linked with 0.25–1.00% (w/v) zeolitic imidazolate framework-8 (ZIF-8) to improve interfacial compatibility and enhance the structural integrity of the film matrix. The formation of hydrogen bonds and electrostatic interactions between ZIF-8 and the Glu/Gly matrix strengthened the chemical network, resulting in increased tensile strength (TS). The water vapor transmission rate (WVTR) of Glu/Gly/ZIF-8 edible films (Glu/Gly/ZIF-8 EF) ranged from 1.085 to 1.453 g/m²/24 h, indicating significantly improved barrier properties. Mechanical testing showed TS and elongation at break (EAB) values of 32.18–60.58 MPa and 211.86–382.83%, respectively, meeting Japanese Industrial Standards for edible films (TS > 0.3 MPa, EAB > 70%, WVTR < 10 g/m²/24 h, thickness < 0.25 mm). Glu/Gly/ZIF-8 EF also demonstrated strong antibacterial activity, with inhibition zones of 25–26 mm for Gram-negative Escherichia coli and 25–34 mm for Gram-positive Staphylococcus aureus. These findings demonstrate that ZIF-8 effectively enhances both the mechanical and functional performance of gluten/glycerol films, providing a promising strategy to expand their application as bioactive packaging materials in the food industry.